2014
DOI: 10.1093/jrr/rru060
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length in Chernobyl accident recovery workers in the late period after the disaster

Abstract: The outcome of the Chernobyl nuclear power plant (CNPP) accident was that a huge number of people were exposed to ionizing radiation. Previous studies of CNPP clean-up workers from Latvia revealed a high occurrence of age-associated degenerative diseases and cancer in young adults, as well as a high mortality as a result of cardiovascular disorders at age 45–54 years. DNA tandem repeats that cap chromosome ends, known as telomeres, are sensitive to oxidative damage and exposure to ionizing radiation. Telomeres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 39 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Several factors such as age, health status, and physiological determinants have been associated with telomere length [16]. Finally, recent studies show that IR exposure causes telomere length shortening in vitro [18] and in vivo [19]. However, the long-term effect of IR on telomere length and its change with age remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors such as age, health status, and physiological determinants have been associated with telomere length [16]. Finally, recent studies show that IR exposure causes telomere length shortening in vitro [18] and in vivo [19]. However, the long-term effect of IR on telomere length and its change with age remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Since telomere maintenance is one of the key events in cancer, it causes activation of the hTERT gene by chromatin remodeling [74] [75]. Reste et al (2014) implicates in their study that in order to initiate the upregulation of telomerase gene, the combined contribution of several conditions viz., a specific mixture of regulating cytokines and a certain confirmation of telomeric ends is required simultaneously [41]. Upregulation of telomerase activity is partly independent of hTERT mRNA expression as in some studies the later was demonstrated to remain unaffected [76] [77].…”
Section: Htert and Hterc-components Of Telomerasementioning
confidence: 99%
“…The telomere is thought to be an internal clock which terminates a cell's life [41]. Telomerase compensates the loss of telomere end sequences during cell division by adding specific DNA repeats at the chromosomal 3' ends [42].…”
Section: Telomerase-a Molecular Insightmentioning
confidence: 99%
“…The Chernobyl nuclear power plant accident forced workers to clean up the region. Some studies revealed high occurrence of age-associated degenerative diseases, cardiovascular disorders, and cancer among them (reviewed by Reste et al [93]). However, when telomere length was analyzed, longer telomeres were found for the workers undertaking excavation and deactivation, and in workers with cancer.…”
Section: Occupational and Environmental Exposuresmentioning
confidence: 99%
“…However, when telomere length was analyzed, longer telomeres were found for the workers undertaking excavation and deactivation, and in workers with cancer. The authors suggest that the exposure to ionizing radiation led to longer telomeres through telomerase activation, which could potentiate carcinogenesis [93]. Even so, it is possible to highlight that most occupational exposures induce telomere shortening.…”
Section: Occupational and Environmental Exposuresmentioning
confidence: 99%